Buddhist votive stele with carved Buddhist figures and inscriptions - Lingley, Kate (Conversations, 2014)
This is a Buddhist votive stele made in the sixth century in north central China. It probably stood either in the courtyard of a Buddhist monastery, or in a public place such as a market square, or at a major crossroads.